Influence of Body Composition on Functional Capacity of Elderly Women with Incidence of Falls - Martins Gervásio, Flávia; Pontes, Geovanna; Santana, Fábio; Liz Policar de Sousa, Barbarah; Nascimento Veloso, Aline Helena (O Mundo da Saúde, 2022)
Functional capacity is an important predictor of quality of life and can be affected by changes in body composition in the elderly, resulting from the aging process itself, with loss of bone mass, muscle mass, and changes in the level of body fat. It is important to analyze the influence of these changes on the decrease of strength and, consequently, its relationship with the incidence of falls, an important factor of functional capacity. The objective of this study was to verify the relationship between body composition and functional capacity in community-dwelling elderly women over 65 years old with or without incidence of falls. This is a cross-sectional and analytical study, sample composed of 77 elderly women divided into two groups, according to the history of falls among fallers (n = 23, mean age 73.6 ± 5.15 years) and non-fallers (n = 54, mean age 71.24 ± 4.92 years). Data were collected age, weight, height, functional capacity through the Sit and Stand Test (SST), as well as body composition, anthropometric measurements, skinfolds, and bone diameters were considered. Later, the comparative study between the faller and non-faller groups in relation to body composition with functional capacity was performed by the T-Student and Mann-Whitney tests. The correlation between the variables body composition and functional capacity and BMI was verified by the Pearson and Spearman tests, adopting the value of (p ≤ 0.05) as significance. A significant difference was identified between the values of functional capacity and bone weight in the group of elderly women with an incidence of falls when compared to the non-faller group (p = 0.002). A weak positive relationship was observed between functional capacity and lean mass weight (r = 0.232, p = 0.021), and functional capacity and bone weight (r = 0.343, p = 0.001) in the elderly women in this study. Among the elderly, aged over 65 years old and with an incidence of falls, bone weight had an influence on functional capacity. The variables of body composition, weight, lean mass, and bone weight are related to functional capacity in community-dwelling elderly women aged over 65 years.